Visible Light-Induced Antibacterial Activity of Pigments Extracted from Dregs of Green and Black Teas. (14th June 2021) - Indrawati, Renny; Zubaidah, Elok; Sutrisno, Aji; Limantara, Leenawaty; Yusuf, Melisa Megawati; Brotosudarmo, Tatas Hardo Panintingjati
Abstract : Chlorophyll and its derivatives are potential natural sensitizers frequently applied in antimicrobial photodynamic therapy. Chlorophyll derivatives are formed naturally during tea processing, but they do not contribute to the color of tea infusions and thus are presumably left in the tea dregs. The present study aimed to investigate (i) the chlorophyll remnants in the pigments recovered from dregs of green and black teas and (ii) the antibacterial activity of pigments extracted from the tea dregs upon illumination using a light-emitting diode (LED) as the light source. Pigment analysis using high-performance liquid chromatography (HPLC) revealed the presence of main degradation products of chlorophylls, such as pheophytin and its epimers, pyropheophytin, and pheophorbides. In vitro assays demonstrated significant reductions in the number of viable bacteria in the presence of the pigments after 30 min of incubation with LED light irradiation. The descending order of bacterial susceptibility was Listeria monocytogenes > Staphylococcus aureus > Escherichia coli > Salmonella typhi . At an equivalent irradiation intensity, the blue and red LEDs could stimulate a comparable inactivation effect through photodynamic reactions. These findings demonstrated the valorization potential of tea dregs as a source of chlorophyll derivatives with visible light-induced antibacterial activity.